Promoting holistic child development: a collaborative school health approach. - Haynes, N.M. (The Journal of school health, 1998)
Keywords: *Child Development; *Health Promotion/og [Organization & Administration]; *Holistic Health; *School Health Services/og [Organization & Administration]; Adolescent; Child; Child Development; Cooperative Behavior; Faculty; Health Promotion; Health Services Needs and Demand; Holistic Health; Humans; School Health Services; Social Support; United States; adolescent; child; child development; cooperation; dept.csp; health promotion; health service; human; organization and management; philosophy; review; school health service; social support; university

School factors in substance abuse prevention among young male African Americans - Haynes, NM; Troutman, MR; Nwachuku, U (Journal of Educational and Psychological Consultation, 1998)
Despite reports that substance abuse among young Americans is on the decline, the problem among young male African Americans continues to be of major concern. School-based prevention strategies offer promising alternatives for reducing the risk factors for substance abuse among this group. The most successful of these programs appear to be those that include the entire school ecology as part of the prevention strategy and focus on the unique psychosocial development needs of these youth. in this article we discuss the prevalence of substance abuse among male African American youth, examine school correlates and risk factors, and review school-based prevention strategies that have shown varying degrees of effectiveness in addressing the substance abuse problems, directly through changing values, attitudes, and behaviors, and indirectly by reducing risk factors and strengthening protective mechanisms.
Keywords: dept.csp